2012
DOI: 10.5194/acp-12-1121-2012
|View full text |Cite
|
Sign up to set email alerts
|

Depositional ice nucleation onto crystalline hydrated NaCl particles: a new mechanism for ice formation in the troposphere

Abstract: Abstract. Sea-salt aerosol (SSA) particles are ubiquitous in the marine boundary layer and over coastal areas. Therefore SSA have ability to directly and indirectly affect the Earth's radiation balance. The influence SSA have on climate is related to their water uptake and ice nucleation characteristics. In this study, optical microscopy coupled with Raman spectroscopy was used to detect the formation of a crystalline NaCl hydrate that could form under atmospheric conditions. NaCl (s) particles (∼1 to 10 µm in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
229
7

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(260 citation statements)
references
References 37 publications
24
229
7
Order By: Relevance
“…The OH-bending modes of water are centered at 1644 cm 1 and 1664 cm 1 , in agreement with previous studies. 5,42,43 Wise et al also reported both the OH-stretching and OH-bending regions of NaCl·2H 2 O at 244 K but the Raman peaks in the OH-stretching region were not resolved in great detail. In addition to the OH-stretching and OH-bending modes reported before, we have observed the librational modes of hydrated NaCl in the low-frequency region (from 200 cm 1 to 800 cm 1 ).…”
Section: B Chemical Composition and Morphology Of Nacl And Ssa Partimentioning
confidence: 99%
See 3 more Smart Citations
“…The OH-bending modes of water are centered at 1644 cm 1 and 1664 cm 1 , in agreement with previous studies. 5,42,43 Wise et al also reported both the OH-stretching and OH-bending regions of NaCl·2H 2 O at 244 K but the Raman peaks in the OH-stretching region were not resolved in great detail. In addition to the OH-stretching and OH-bending modes reported before, we have observed the librational modes of hydrated NaCl in the low-frequency region (from 200 cm 1 to 800 cm 1 ).…”
Section: B Chemical Composition and Morphology Of Nacl And Ssa Partimentioning
confidence: 99%
“…The latter can serve as an efficient ice nucleating particle and might be essential for the microphysics of high altitude marine clouds. 4,5,7,8 According to the bulk phase diagram of NaCl/water, anhydrous NaCl is the thermodynamically stable phase formed upon efflorescence of solution above 273.3 K. 9,10 Below this peritectic temperature, the dihydrate form is more stable. However, measurements performed with submicron droplets have shown that sodium chloride dihydrate does not form at alexei.kiselev@kit.edu temperatures above 253 K. 11 A similar observation was made by Koop et al, who studied the efflorescence and deliquescence behavior of micron-sized droplets of NaCl solution and found that NaCl dihydrate was only formed via heterogeneous nucleation on available surfaces of ice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to participate in electrostatic interactions may then be added as a characteristic of a good IN, beyond the ability to bond simply with hydrogen (Pruppacher and Klett, 1997). Indeed, it may be for this reason that soluble salts, such as ammonium sulfate and sodium chloride, have been shown to show deposition IN abilities, provided that the temperature is below their eutectic Wise et al, 2012).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%